Inventory of Portuguese-based Intangible and Tangible Heritage in Larantuka and Sikka (Maumere) in Flores Island (Indonesia): Legacies and Realms of Memory of Portuguese Eurasian Communities in a Muslim Country - Morais, Isabel; Baxter, Alan N. (University of Saint Joseph, 2018)
A study of Portuguese cultural vestiges assimilated into the local cultures of the island of Flores, in Eastern Indonesia, and maintained today. The vestiges include, principally, street theatre (the Bobo tradition) as well as ritual traditions inherited through the Confraternities established by Dominican missionaries in the 16th century.

nventory of Portuguese-based Intangible and Tangible Heritage in Larantuka and Sikka (Maumere) in Flores Island (Indonesia): Legacies and Realms of Memory of Portuguese Eurasian Communities in a Muslim Country [Research Report] - Morais, Isabel; Baxter, Alan (University of Saint Joseph, 2018)